S-cone-specific circuitry in the outer plexiform layer of a cone-dominant mammal - Yizhen Z. Zhang; Shan Chen; Haohua Qian; Wei Li; John M. Ball (Proceedings of the National Academy of Sciences, 2025)
In the vertebrate retina, short wavelength-sensitive S-cones and their downstream interneurons play unique roles in both image forming and non-image-forming vision. Due to their conserved relative rarity in the retina and the high density of rods found in many model species, S-cone circuitry is challenging to examine in detail. Here, we combine electrophysiology, high-quality 3D electron microscopy reconstruction, and electroretinography to characterize in fine detail the S-cone selective circuitry in the outer plexiform layer (OPL) of the cone-dominant retina of the thirteen-lined ground squirrel (13-LGS). The 13-LGS retina has no S-OFF bipolar cell, and both horizontal cell types show distinct S-cone preferences. Signal processing in the 13-LGS OPL appears to have evolved for separate channels that independently modulate synaptic sensitivity of S- and M-cone networks.